EVALUATION OF EROSION AND SILTATION OF LAKE TONDANO BASED ON THE HYDROLOGICAL AND SOIL CHARACTERISTICS OF ITS CATCHMENT - HIKMATULLAH, .; H, SUBAGYO; KURNIA, UNDANG; AMIEN, LE ISTIQLAL (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2000)
The lake Tondano in North Sulawesi Province, has very important role, namely as the source of domestic water use for Manado town, electric power generator, fisheries, and tourism. It has been issued to serious siltation process over the tolerable Iimit due to soil erosion, so that the water quantity and quality are worried to be decrease. The objective of the research is to study the possibility occuring of lake siltation caused by soil erosion, by analyzing the hydrological and soil characteristics data from the Tondano catchment. The hydrological data analysis includes the river discharge and sediment discharge entering the lake, lake depth, and lake water balance. The soil data analysis consists of chemical and physical soil properties, soil infiltration rate, and erosion hazard of the catchment predicted by universal soil loss equation (USLE) method. The results indicate that the water lake level fluctuation and the outlet discharge depend on the amount of rainfall. The discharge of sediment suspension entering the Jake was 7,540 tons per year compared to the lake volume as much as 680 millions m3, the lake would be full-filled by the sediments in thousands of years. The measured deepest lake depth at present is about 22 m, and during the last century, the lake was decrease as much as 6 m. The infiltration rate of main soils varies from moderate to very rapid (22- 71 cm/hr), and are still higher than the maximum absolute rainfallintensity, so that overland flow occurs very little. The amount of soil loss by erosion indicates that 94% of the catchment area is lower than the maximum tolerable limits (< 12 t/ha/yr). This research has proved that the hydrological and soil condition of the Tondano catchment have not yet been serious degradation caused by erosion, so that the accelerated siltation due to erosion process was not occur in the lake catchment and its surrounding.